Fields and Facebook: Ta’ayush’s Grassroots Activism and Archiving the Peace that Will Have Come in Israel/Palestine - Simons, Jon (2016)
Israeli peace activism has increasingly taken place on new media, as in the case of the grassroots anti-Occupation group, Ta’ayush. What is the significance of Ta’ayush’s work on the ground and online for peace? This article considers the former in the light of social movement scholarship on peacebuilding, and the latter in light of new media scholarship on social movements. Each of those approaches suggest that Ta’ayush has very limited success in achieving its strategic goals or generating outrage about the Occupation in the virtual/public sphere. Yet, Ta’ayush’s apparent “failure” according to standard criteria of success misses the significance of Ta’ayush’s work. Its combination of grassroots activism and online documentation of its work in confronting the Occupation in partnership with Palestinians has assembled an impressive archive. Through the lens of Walter Benjamin’s philosophy of history, Ta’ayush can be seen to enact a “future perfect” peace that will have come.